Dynamics of the Moving Ring Load Acting in the System Hollow Cylinder plus Surrounding Medium with Inhomogeneous Initial Stresses - Akbarov, Surkay D.; Bagirov, Emin T.; Ozisik, Muslum (TECH SCIENCE PRESS, 2019)
This paper studies the influence of the inhomogeneous initial stress state in the system consisting of a hollow cylinder and surrounding elastic medium on the dynamics of the moving ring load acting in the interior of the cylinder. It is assumed that in the initial state the system is compressed by uniformly distributed normal forces acting at infinity in the radial inward direction and as a result of this compression the inhomogeneous initial stresses appear in the system. After appearance of the initial stresses, the interior of the hollow cylinder is loaded by the moving ring load and so it is required to study the influence of the indicated inhomogeneous initial stresses on the dynamics of this moving load. This influence is studied with utilizing the so-called three-dimensional linearized theory of elastic waves in elastic bodies with initial stresses. For solution of the corresponding mathematical problems, the discrete-analytical solution method is employed and the approximate analytical solution of these equations is achieved. Numerical results obtained within this method and related to the influence of the inhomogeneous initial stresses on the critical velocity of the moving load and on the response of the interface stresses to this load are presented and discussed. In particular, it is established that the initial inhomogeneous initial stresses appearing as a result of the action of the aforementioned compressional forces cause to increase the values of the critical velocity of the moving load.
Keywords: Inhomogeneous initial stresses; dynamics of a moving load; critical velocity; hollow cylinder; elastic medium; ring load; COMPRESSIBLE VISCOUS-FLUID; CYLINDRICAL-SHELL; WAVE-PROPAGATION; ELASTIC PLATE; HALF-SPACE; INTERIOR; VIBRATION; TUNNEL; Computer Science; Materials Science